Integration of PV Arrays in DC Power Grids via Unidirectional Boost Converters: A PBC Approach (2018)
This paper presents a general control design for photovoltaic systems integrated with Direct-Current power grids by using an unidirectional boost converter. Passivity-based control (PBC) theory is used as a control technique since the dynamical model of the boost converter has an intrinsically port-Hamiltonian structure, where PBC theory is based upon, to design stable controllers via Lyapunov stability theory. To control the photovoltaic solar system, a current control mode is used, since photovoltaic cells are mathematically modelled as current sources, where the photo-current determined by the solar irradiance and the cell's temperature. Proportional and proportional-integral passivity-based controllers are developed to operate the boost converter under current control mode to extract the maximum power available in the PV array. Simulation results are conducted via MATLAB/ODE-package software. © 2018 IEEE.